Attitudes to death in surgeons and internists - Antonio Rodríguez Sánchez (ECIMED, 2021)
Introduction: Death in the hospital context is a critical stressor; for the doctor in his care, is part of the professional role, producing different coping attitudes. Objective: To compare the attitudes to death in surgeons and internists of clinical-surgical hospital. Methods: Quantitative, descriptive and cross-sectional research conducted in August 2019, in an intentional sample of 30 surgeons and 33 internists. The Attitudes to Death Questionnare-2 was used, composed of 32 items distributed in 6 subscales. Results: There were disagreements with having religious attitudes both surgeons and internists. There were no anxiety attitudes towards death as well as pro-euthanasia attitudes. Undefined positions were identified in relation to professional distancing attitudes. There was ambiguity regarding attitudes of affective vulnerability and evasion before death. There was no association between age and professional experience with respect to the attitudes characterized. Conclusions: The attitudes to death between surgeons and internists were characterized by being predominantly homogeneous. No type of relationship was found between the sociodemographic variables age and work experience with respect to attitudes towards death.